2022
DOI: 10.3389/fsurg.2022.968372
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual misoprostol vs. oral misoprostol solution for induction of labor: A retrospective study

Abstract: IntroductionInduction of labor (IOL) is one of the most common obstetrical procedures, with an increasing rate. The prostaglandin E1 analogue misoprostol is frequently used as a primary method of labor induction. The optimal dose and route of administration is yet to be ascertained.AimTo compare efficiacy and safety between a regimen of sublingually administered misoprostol and a regimen of orally administered misoprostol, with cesarean delivery as primary outcome.MethodsA retrospective study was conducted inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Ifariola et al [ 12 ] reported that the induction‑delivery interval was 10.02±2.37 hours in the sublingual group. Mahdi et al [ 23 ] conducted a retrospective study of 2404 women with oral and sublingual misoprostol over a period of five years. They concluded that sublingual misoprostol was associated with a significantly shorter induction to vaginal delivery time.…”
Section: Discussionmentioning
confidence: 99%
“…Ifariola et al [ 12 ] reported that the induction‑delivery interval was 10.02±2.37 hours in the sublingual group. Mahdi et al [ 23 ] conducted a retrospective study of 2404 women with oral and sublingual misoprostol over a period of five years. They concluded that sublingual misoprostol was associated with a significantly shorter induction to vaginal delivery time.…”
Section: Discussionmentioning
confidence: 99%